Psysical activity and sedentary lifestyle in children with type 1diabetes: a multicentre Italian Study - Fainardi, V.; Scarabello, C.; Cangelosi, A.; Fanciullo, L. (Acta Biomedica Atenei Parmensis, 2011)
Background: Regular Physical Activity (RPA) is one of the cornerstones of Type 1 Diabetes (T1D) therapy, but conflicting results are reported in the literature. Aim: To compare (RPA) and Sedentary Lifestyle (SL) among children with type 1 diabetes (T1D) and healthy peers. Subjects and Methods: Seven Italian paediatric diabetes centres enrolled 129 children with T1D and 214 healthy peers who were interviewed by a telephone questionnaire on physical activity level, sedentary lifestyle and clinical data. Results: Compared to healthy peers, children with T1D: performed the same amount of RPA, were more frequently engaged in team sports (p=0.018), described RPA as an enjoyable activity (p=0.033), not boring (p=0.035), a chance to spend time with peers (p=0.033) and to meet new friends (p=0.016). Children with T1D were finally used to consume less snacks during watching TV (p